2019
DOI: 10.3390/fi11080169
|View full text |Cite
|
Sign up to set email alerts
|

An Image Feature-Based Method for Parking Lot Occupancy

Abstract: The main scope of the presented research was the development of an innovative product for the management of city parking lots. Our application will ensure the implementation of the Smart City concept by using computer vision and communication platforms, which enable the development of new integrated digital services. The use of video cameras could simplify and lower the costs of parking lot controls. In the aim of parking space detection, an aggregated decision was proposed, employing various metrics, computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…However, their approach can be used for data collection. Similarly, Tȃtulea et al [16] detected the parking spaces and identified if the parking spots are occupied or available using computer vision techniques and the camera as a sensor. In order to do that, they performed different steps, including Frame Pre-processing, Adaptive Background Subtraction, Metrics & Measurements, History Creation, Results Merging for Final Classification, and Parking Space Status.…”
Section: Related Workmentioning
confidence: 99%
“…However, their approach can be used for data collection. Similarly, Tȃtulea et al [16] detected the parking spaces and identified if the parking spots are occupied or available using computer vision techniques and the camera as a sensor. In order to do that, they performed different steps, including Frame Pre-processing, Adaptive Background Subtraction, Metrics & Measurements, History Creation, Results Merging for Final Classification, and Parking Space Status.…”
Section: Related Workmentioning
confidence: 99%
“…Parking situations were estimated by applying machine learning. Research that was conducted in [41] uses video camera sensors for detecting multiple parking space occupancy. Using image processing techniques: the Histogram of oriented Gradient (HOG) descriptor, the Scale-invariant feature transform (SIFT) corner detector, and Metrics on Color Spaces YUV, HSV, and YCrCb authors achieved an accuracy rate of over 93% for parking lot occupancy detection.…”
Section: State Of the Artmentioning
confidence: 99%
“…In this short communication, we propose a feasible solution for heavy goods vehicle detection. Computer Vision algorithms have been implemented for various tasks in traffic monitoring for many years, e.g., traffic sign recognition [1][2][3][4][5][6][7]; intelligent traffic light system [8]; vehicle speed monitoring [9]; traffic violation monitoring [10]; vehicle tracking [11][12][13]; vehicle classification [14][15][16][17][18][19][20][21][22][23][24][25][26]; vehicle counting system on streets and highways [27][28][29][30][31]; parking spot detection from the point of view of the car for parking assistants [32,33]; and parking spot monitoring [34][35][36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: Introductionmentioning
confidence: 99%